Empleo de los corticoesteroides en el tratamiento de la tuberculosis pleural exudativa - Llosa Garcia, Javier (1972)
Results obtained with joint administration of streptomycine isoniazid and corticosteroids (30 mg, of prednisone per day during 5 days = 150 mg.) are given on 20 patients treated for TBC pleural effusion, at the General Hospital of Arequipa, Perú, in the period 1967 - 1971.  Effects reached were favorable upon characteristics and dissaperance of the effusion as well on the patient's clinical symptoms, evolution of the process and shortening of hospitalization period.